The Binding Authority of the Laws of Previous Religious Communities (shar’ man qablanā) and the Derivation of Their Rulings - Mohammaed, Sabreen Ali; Makky, Rand Sa’ad (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This study explores the jurisprudential rule "The Sharia of those before us is also binding upon us" (Sharʿ man qablanā), analyzing its authenticity, applications, and implications within Islamic jurisprudence. The research begins by establishing the scholarly positions on the rule's acceptance, highlighting the divergence between those who view previous religious laws as binding upon Muslims unless explicitly abrogated and those who reject such application. The study employs a descriptive-analytical approach, drawing on Quranic verses, Prophetic traditions, and scholarly interpretations to assess the rule’s legal standing. It examines historical examples of previous legislations mentioned in Islamic sources and evaluates their applicability in Islamic law. The paper emphasizes the need for careful scrutiny in determining whether such rulings align with the principles of Islamic Sharia and are supported by clear textual evidence. The conclusion stresses that while some pre-Islamic rulings may be upheld when consistent with Islamic objectives, their application must not contradict established Islamic principles. This nuanced approach ensures the integrity and adaptability of Islamic jurisprudence.